Objective vs. perceived maternal smartphone use and observed mother-infant interaction quality - Ventura, Alison K.; Wolfers, Lara N.; Coyne, Sarah M.; Pfafman, Rachel; Uva, Sabrina; Ceja Almontes, Karla I.; Shinde, Aniruddha S.; Galovan, Adam M.; McDaniel, Brandon T. (Frontiers in Developmental Psychology, 2025)
IntroductionPrior research links maternal smartphone use to reduced sensitivity and responsiveness to infant cues, but emerging evidence suggests that mothers' perceptions of their smartphone use - such as feelings of empowerment or distress - may also shape the quality of mother-infant interactions. This study examined how both objective and perceived smartphone use related to mother-infant interaction quality in naturalistic settings.MethodParticipants were 147 mother-infant dyads from a longitudinal study of smartphone use and infant development. When infants were 2 months old, mothers completed 5 days of ecological momentary assessment (EMA), reporting time spent with their infant, perceived smartphone-related interruption (technoference), distress, and empowerment. Mothers' smartphone use was monitored continuously across the 5 day EMA period via installed mobile applications. Dyads also participated in a feeding observation; videos were later coded to assess overall interaction quality and dyadic contingency, both derived from six domain-specific subscales representing mothers' and infants' contributions to the interaction. Multivariable regression examined associations between mother-infant interaction quality and mothers' typical level of smartphone use around their infants, perceived technoference, smartphone-related distress, and smartphone-related empowerment.ResultsGreater smartphone-related empowerment was positively associated with greater engagement of the infant in socioemotional growth fostering experiences, greater infant clarity of cues and responsiveness to the mother, better dyadic contingency, and greater overall interaction quality. No significant associations were found for typical level of smartphone use, perceived technoference, or smartphone-related distress.DiscussionHow mothers feel about their smartphone use - particularly feelings of empowerment - may be more closely related to the quality of their interactions with their young infants than the amount or perceived negative impacts of their smartphone use.